Nanopore sequencing of infectious fluid is a promising supplement for gold-standard culture in real-world clinical scenario - Zhao, Manna; Zhang, Yongyang; Chen, Li; Yan, Xuebing; Xu, Tianmin; Fu, Maoying; Han, Yangguang; Zhang, Ying; Zhang, Bin; Cao, Juan; Lin, Jing; Shen, Dan; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction: Infectious diseases are major causes of morbidity and mortality worldwide, necessitating the rapid identification and accurate diagnosis of pathogens. While unbiased metagenomic next-generation sequencing (mNGS) has been extensively utilized in clinical pathogen identification and scientific microbiome detection, there is limited research about the application of Nanopore platform-based mNGS in the diagnostic performance of various infectious fluid samples. Methods: In this study, we collected 297 suspected infectious fluids from ten clinical centers and detected them with conventional microbiology culture and Nanopore platform-based mNGS. The objective was to assess detective and diagnostic performance of Nanopore sequencing technology (NST) in real-world scenarios.Results: Combined with gold-standard culture and clinical adjudication, Nanopore sequencing demonstrated nearly 100% positive predictive agreements in microbial-colonized sites, such as the respiratory and urinary tracts. For samples collected from initially sterile body sites, the detected microorganisms were highly suspected pathogens, and the negative predictive agreements were relatively higher than those in the microbial-colonized sites, particularly with 100% in abscess and 95.7% in cerebrospinal fluid. Futhermore, consistent performance was also observed in the identification of antimicrobial resistance genes and drug susceptibility testing of pathogenic strains of Escherichia coli, Staphylococcus aureus and Acinetobacter baumannii.Discussion: Rapid NST is a promising clinical tool to supplement gold-standard culture, and it has the potential improve patient prognosis and facilitate clinical treatment of infectious diseases.